2022
DOI: 10.1371/journal.pbio.3001797
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-promoting neurons remodel their response properties to calibrate sleep drive with environmental demands

Abstract: Falling asleep at the wrong time can place an individual at risk of immediate physical harm. However, not sleeping degrades cognition and adaptive behavior. To understand how animals match sleep need with environmental demands, we used live-brain imaging to examine the physiological response properties of the dorsal fan-shaped body (dFB) following interventions that modify sleep (sleep deprivation, starvation, time-restricted feeding, memory consolidation) in Drosophila. We report that dFB neurons change their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Thus, we hypothesized 060B, PPL1-γ2,α1, PPL1-α’2α2, PPL1-α’3 and PPL1-α3-projecting DANs may display changes in activity in the AM vs. PM. To test this hypothesis, we expressed the cyclic adenosine monophosphate (cAMP) sensor, UAS- Epac1-camps , in 060B neurons and used high throughput live brain imaging to monitor neuronal responses to bath-applied DA in the AM or PM from cell bodies (Figure 2I) ( 14, 96, 97 ). As seen in Figure 2I-J, 060B cell bodies showed robust increases in FRET signaling in the AM compared to the PM.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we hypothesized 060B, PPL1-γ2,α1, PPL1-α’2α2, PPL1-α’3 and PPL1-α3-projecting DANs may display changes in activity in the AM vs. PM. To test this hypothesis, we expressed the cyclic adenosine monophosphate (cAMP) sensor, UAS- Epac1-camps , in 060B neurons and used high throughput live brain imaging to monitor neuronal responses to bath-applied DA in the AM or PM from cell bodies (Figure 2I) ( 14, 96, 97 ). As seen in Figure 2I-J, 060B cell bodies showed robust increases in FRET signaling in the AM compared to the PM.…”
Section: Resultsmentioning
confidence: 99%
“…Why, then, does this protocol not cause an effect in dFB 23E10□84C10 neurons? Previous studies have demonstrated that the dFB is under strong dopaminergic inhibition (15, 17, 20, 44) and that dopamine is a key factor regulating whether dFB neurons are active or silent (20). In addition, it was shown that sleep deprivation increases the activity of dFB neurons, switching them to the active state (16).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the Dopamine 1-like receptor 1 ( Dop1R1 ) is not expressed in the sleep-promoting dorsal Fan Shaped Body neurons in healthy adults [86]. However, following starvation or time restricted feeding the Dop1R1 is recruited to the dorsal Fan Shaped body to provide additional inhibitory tone to sleep promoting neurons [87]. Finally, a sleep circuit that is primarily active during a narrow developmental time-window can be reactivated in adults when flight is impaired [88].…”
Section: Discussionmentioning
confidence: 99%